ANALISIS TANDA TUBUH DALAM NOVEL THE HUNGER GAMES: CATCHING FIRE KARYA SUZANNE COLLINS - TAMBAANI, EVANS GRIFIT (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â This study entitles â€œAnalisis Tanda Tubuh dalam Novel The Hunger Games: Catching Fire Karya Suzanne Collinsâ€ . Semiotics is a study about signs. The signs of body are signs produced by, through, or that are in the body. The sign of body is one of nonverbal semiotic. Using the sign of body in communication is very important to support the delivery of verbal messages. This study is an attempt to identify, classify, and analyze the body sign contained in the novel. The data are collectedÂ through the authorâ€™s explanation about the use of the body as a conduit of information. The writer uses theory of Danesi to identify and classify the data. In analyze the data, the writer used the theory of Barthes which states that connotation is a new meaning that gives user the sign in accordance with wishes, background of knowledge, or a new convention that exists in a society. The results of this research show that based on the theory of Danesi there are seven sign of body contained in the novel. Those are signals, facial expression, eye contact, body language, touch, gesture and dancing. The meanings contained in the signs of body are to attract attention, fear, worry, appreciation farewell, discomfort, pain, acting, lies, surprise, happiness, frustration, demand, shame, victory, relief, confusion, feeling guilty, resentment, understand each other, thinking, caring, vigilant, doubt, pride, the origins, state of the body, teasing, sadness, the event will begin, rebellion, refrain, affection, approval, admiration, gratitude, seriousness, providing support, warning, clear the mind, rejection, invitation, respect, ridicule and anger. The writer hopes that this study will help the reader in understanding about semiotic study especially sign of body as one of nonverbal sign and how it works in communication. Keywords: The Sign of Body, Nonverbal Semiotic, Semiotic Analyze, Novel The Hunger Games: Catching Fire